Corporate Governance Structures, Ethical Decision-Making and Long-Term Business Success: A Comprehensive Review - Kashif Lodhi; Dr Atif khan; Gianfranco Rusconi; Sohail Ahmad (Corresponding Author) (`, 2025)
This comprehensive review looks at the complex interconnection between corporate governance structures, ethical decisions, and their significant influence on the development of the company success. Corporate governance is a concept that deals with the regulation of organizations with a purpose of protecting the interests of all the buyers. Main aspects of corporate governance are outlined and exemplified, such as structure of the board of directors, the active role of shareholders, independent executive compensation, ethics, whistleblowing, transparency, accountability, stakeholder management, risk, and their impact on sustainable success. The general message running through the entire review is on the significant correlation between the two concepts of ethical governance and Sustainable business model. The alignment of ethical values with governance practices is not only a guarantor of ethical behavior but also for improved financial performance, as well as reputation and brand value. It promotes decision making that continues to stakeholder emergence, management of risks, and corporate social responsibility, which leads to an organization’s viability and competitiveness. The review reveals that more companies are embracing the need to respect ethical governance principles and practice responsible business to ensure their sustainability in the market. In this context, several prospective directions for the further study are described. These are: Cross cultural worldview, empirical research on communicating the effects of governance and ethical practices, a focus on how technology can foster good governance and the use of ethical governance model for SMEs. Further, the paper recommends research on policy and regulation, methodologically long-term investigations of the interaction between governance, ethics, and sustained performance, as well as case level research on organizations ethical governance as part of their corporate culture. The knowledge, therefore, of the relationship between corporate governance, ethical issues, and ultimate organizational success in a dynamic business environment is critical for organizations ‘proponents of sustainable organizational success. Thus, this review proves productive by integrating prior research and promising case studies, proving recommendations on how firms can develop their governance and ethical systems to build a prosperous organization. Keywords: Complex interconnection, corporate governance structures, ethical decisions, influence, development, company success